Dayah, the Traditional Islamic Education System of Aceh 1900-2000 - Stephen Roche (Sharia and Law Faculty, 2012)
This article is an extract from my dissertation which offers a historiography of the Dayah, Aceh’s traditional institution of Islamic education and picks up at the point of Aceh’s history where its Dutch colonial experience began. The section presented here details some of the theological, philosophical and political factors that contributed to the development of the regions current variety of educational institutions. However, despite the effects of such historical and ongoing developments, that continue to inform the theological understanding and social concerns of Aceh’s ulama, the Dayah still manages to represent a distinct Muslim identity that express the richest cultural heritages of the region within an orthodox religious framework. Therefore, the Dayah of Aceh continues the traditional Islamic educational experience for the Muslims of the region despite the historical and ongoing influence of cultural, political and social developments.